Alternatives to detention: ‘open family units’ in Belgium - Schockaert, L (Refugee Studies Centre, University of Oxford, 2013)
Preliminary outcomes of an alternative to detention programme in Belgium, based on case management and individual ‘coaches’ for families, are positive and merit consideration by other countries